Linking mango infestation by fruit flies to fruit maturity and fly pressure: A prerequisite to improve fruit fly damage management via harvest timing optimization. (August 2021) - Grechi, Isabelle; Preterre, Anne-Laure; Caillat, Aude; Chiroleu, Frédéric; Ratnadass, Alain
Abstract: Fruit flies (Diptera: Tephritidae) are considered to be major pests of mango ( Mangifera indica ) worldwide. Their management, with an increasing focus on replacing synthetic pesticides with alternative pest control methods, is a challenging issue. A study was carried out from 2015 to 2017 in Reunion Island under field conditions in order to characterize the incidence of fruit flies on mango production and to link fruit fly infestation with fruit maturity and fly pressure. Mango fruits were mainly infested by Bactrocera zonata . Few fruits were infested by Ceratitis quilicii, and even fewer by Ceratitis capitata . Infestation increased as fruits ripened. Less than 4% of the fruits were infested at the green, green-mature and early yellow-point stages. Infestation increased to 10–11% at later yellow-point stages, and reached 14–16% at ripe and overripe stages. Fruit infestation was closely related to changes in the peel texture (firmness, in particular) and chlorophyll fluorescence of the fruit as it ripened. Whereas variability in fruit fly abundance in traps was observed between orchards and years, it did not clearly explain variability in fruit infestations, which was mostly explained by variability in fruit maturity. The study suggests that fruit fly trapping is not adequate to assess infestation risk or to guide management decisions, but instead provides evidence that fruit fly damage could be reduced by adjusting harvest timing, especially by harvesting fruits at the green-mature stage or at the yellow-point onset. Highlights: Mango infestation by fruit flies increases with fruit maturity. Infestation is related to alterations in peel texture and chlorophyll fluorescence. Fruit infestation is poorly related to fruit fly catches in traps. Adjusting harvest timing is a relevant method to manage fruit fly damage on mango.